Readiness and willingness of Malaysian community pharmacists in providing vaccination services - Wei Chern Ang; Mohamad Syafuan Fadzil; Fatin Najihah Ishak; Nassrah Norissya Adenan; Mohamad Haniki Nik Mohamed (Taylor & Francis Group, 2022)
Background Vaccination is an effective public health intervention in reducing morbidity and mortality of infectious diseases. Compared to other countries where community pharmacists (CPs) administer vaccines, CPs in Malaysia are not authorised. This study aimed to assess CPs' readiness and willingness to provide vaccination in Malaysia, identify potential barriers to and factors supporting the provision of this service. Methods A cross-sectional study was conducted among Malaysian CPs from April to June 2021. A validated online questionnaire was distributed through social media, instant messaging, email, and pharmacy societies. Results Of 492 CPs recruited throughout Malaysia, 439 (89.2%) expressed willingness to provide vaccination services to the public, 403 (81.9%) agreed with the accessibility of community pharmacies to the public, and 73.4% agreed that their role in vaccination could help to improve the overall vaccination coverage rate. The lack of pharmacist training in vaccination and concerns on maintaining patient safety were identified as barriers to CPs' implementation of vaccination services, with 52.8% and 47.8% of them agreeing, respectively. Training sessions and operational guidelines on providing vaccination services are required to overcome the barriers. Conclusion CPs in Malaysia were ready and willing to provide vaccination services to the public. However, the implementation demands training workshops and re-evaluation of CPs in public vaccination programmes by Malaysian healthcare policymakers.